Stress-assisted atomic diffusion in metastable austenite D03 phase of Cu-Al-Be shape memory alloys. (November 2016) - López-Ferreño, I.; Breczewski, T.; López, G.A.; Nó, M.L.; San Juan, J.
Abstract: Cu-Al-based shape memory alloys are firm candidates to be used up to 473 K. The main limiting aspect is the activation of diffusion processes in the metastable austenite phase, which drive the alloy decomposition. In the present work the study of short-distance diffusion processes has been approached by internal friction. A relaxation peak has been found in the metastable β (D03 ) phase of a Cu-Al-Be shape memory alloy, around 500 K (at 1 Hz), with an activation energy of E a = 1.38 ± 0.05 eV. An atomic mechanism of elastic dipoles Antisite-Vacancy reorientation, involving stress-assisted short distance Cu-atoms diffusion, has been proposed. Graphical abstract: